Implementation of Web-Based Teaching Media as an Effort to Utilize Digital Technology in Learning - Yulianti, Dewi; Suriansyah, Ahmad; Harsono, Arta Mulya Budi; Ridhaningtyas, Latifa Putri; Noorhapizah, Noorhapizah (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
This study aims to analyze the implementation of web-based teaching media at SDN SN Surgi Mufti 1, Banjarmasin, to improve the quality of education. Qualitative methods with a case study approach are used by involving questions and answers to the principal, teachers, and students. The results show that digital technology in learning can increase student interest, motivation, understanding, and make the learning process more interactive. However, challenges such as funding, time management, and inadequate infrastructure still exist. Policy supports and training for teachers are essential to overcome these obstacles. Research emphasizes that the implementation of web-based teaching media has good potential when creating an interesting and effective learning environment, which is in line with technological developments in the digital era